Preventive Efforts for Covid-19 Transmission to Traders in RT 25 Air Hitam Village, Samarinda - Rina Tri Agustini; Alesandra Dufer Fandrias; Lince Yikwa (ABDIMAYUDA: Indonesia Journal of Community Empowerment for Health, 2022)
The application of health protocols, especially the use of masks has decreased, this was seen from the number of people who feel lazy and saturated to apply the use of masks when outdoors such as when trading. Therefore, the awareness and understanding of traders needs to be increased through the provision of education to prevent the transmission of Covid-19. Activities carried out in Air Hitam Village, Samarinda Ulu, were started from the identification of public health problems in traders related to Covid-19, data retrieval and processing, planning activities that are then implemented, and evaluation of activities. The priority of the problems found was the decrease in public awareness, especially traders related to the implementation of health protocols, especially the use of masks. Providing education to traders regarding efforts to prevent Covid-19 by implementing health protocols was carried out through preventive packages in the form of distributing masks and handwashing soap, poster about good and correct hand washing, and banner for mandatory mask areas. Traders have understood the prevention efforts delivered through preventive package programs and some of them have implemented it every day.